Boston Children's Hospital approach to brachial plexus birth palsy. Issue 4 (July 2016) - Vuillermin, Carley; Bauer, Andrea S.
Abstract : The treatment of infants with brachial plexus birth palsy (BPBP) continues to be a focus at Boston Children's Hospital. Over the last 15 years, there have been many developments in the treatment of infants with BPBP. Some of the greatest changes have emerged through technical advances such as the advent of distal nerve transfers to allow targeted reinnervation as well as through research to understand the pathoanatomical changes that lead to glenohumeral dysplasia and how this dysplasia can be remodeled. This review will discuss our current practice of evaluation of the infant with BPBP, techniques for microsurgical reconstruction, and prevention and treatment of secondary glenohumeral dysplasia.